Illocutionary Acts Found in Rachel’s Utterances the Main Character of I Am Not Ashamed Movie - Gabriella Samantha Valerian; Sujana Sujana (JEdu: Journal of English Education, 2021)
This article aims to identify the types and functions of illocutionary acts in the main character’s utterances in “I Am Not Ashamed” movie. The theory used in this article is theory of illocutionary acts proposed by Searle (1976) who classified the types of illocutionary acts into five types, there are representatives, directives, commissives, expressives, and declaratives. The method in this article using a qualitative descriptive method.  The result of this study there are 4 types of illocutionary acts such as representatives, descriptives, commissives, expressives and 36 of functions of illocutionary acts there are describing, stating, inform, assert, claim, believe, conclude, tell, agree, guess, assure, remind, urging, forbiding, ask, requesting, begging, questioning, inviting, suggesting, warning, promising, planning, offering, threatening, surprise, thank, apology, annoyed, curious, greet, disappointment, worried, like, satisfied, and praise in the main character’s utterances in “I Am Not Ashamed” movie.